Study on the Performance and Carbon Emission of Geopolymers Concrete - Zhu, Lixin (Transactions on Engineering and Technology Research, 2024)
As the global demand for reducing carbon emissions increases, the construction industry must seek environmentally friendly alternative materials. Geopolymers concrete, as a low-carbon and environmentally friendly material, has emerged as a potential alternative to cement concrete due to its excellent mechanical properties and environmental adaptability. This paper focuses on geopolymers concrete, exploring its applications, mechanical properties, and carbon emissions. Firstly, the composition, reaction mechanism and application prospect of geopolymers concrete are systematically analyzed. Then, the mechanical properties of cement concrete are studied, and its superior compressive strength, high temperature resistance and corrosion resistance compared with traditional cement concrete are highlighted. Finally, the carbon emissions in the production process are discussed in detail, and the effects of different raw materials and production methods on carbon emissions are compared. It is shown that the carbon emissions of geopolymers concrete are significantly lower than that of traditional cement concrete. The research concludes that geopolymers concrete not only has significant environmental benefits but also possesses strong mechanical properties and excellent durability, showing great potential for applications in green buildings, marine engineering, and refractory materials. In the future, by reducing production costs, optimizing processes, and promoting standardization, geopolymers concrete is expected to become an important green material in the construction industry, contributing to the achievement of global carbon reduction goals.